Carbohydrates@MOFs. Issue 5 (7th March 2019) - Astria, Efwita; Thonhofer, Martin; Ricco, Raffaele; Liang, Weibin; Chemelli, Angela; Tarzia, Andrew; Alt, Karen; Hagemeyer, Christoph E.; Rattenberger, Johannes; Schroettner, Hartmuth; Wrodnigg, Tanja; Amenitsch, Heinz; et al.
Abstract : MOFs have demonstrated outstanding properties for the protection and controlled release of different bio-entities, from proteins to living cells. Abstract : MOFs have demonstrated outstanding properties for the protection and controlled release of different bio-entities, from proteins to living cells. Carbohydrates, as pure molecules or as a component of proteins and cells, perform essential biological functions. Thus, an understanding of the role of carbohydrates in the formation of MOF-based bio-composites will facilitate their application to biotechnology and medicine. Here, we investigate the role of carbohydrate molecular weight and chemical functionalization in the formation of carbohydrate@MOF composites. We find that chemical functionalization, such as carboxylation, that leads to an enhancement of metal cation concentration at the surface of the molecule triggers the rapid self-assembly of the MOF material, zeolitic-imidazolate framework 8 (ZIF-8). Furthermore, we determine the encapsulation efficiency and measure the release properties of the carbohydrate under controlled conditions. Our findings show that MOFs can be used to prepare a new class of biocomposites for the delivery of carbohydrate-based therapeutics.